2011
DOI: 10.3382/ps.2011-01366
|View full text |Cite
|
Sign up to set email alerts
|

Gas mixtures approach to improve turkey meat shelf life under modified atmosphere packaging: The effect of carbon monoxide

Abstract: Gas mixtures with CO have been applied to beef and pork meat, but no data have been reported regarding their application to poultry meat. The aim of this study was to evaluate the effect of an anaerobic gas mixture with CO on the growth of spoilage flora, color, and lipid oxidation stability of turkey meat under modified atmosphere packaging (MAP) stored at 0°C. Sliced meat samples were individually packaged under aerobiosis (aerobic packaging) and in 4 different modified atmospheres containing different gas m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This result was consistent with Maqsood et al (2016), in which L * values of camel meat remained the same ( p > 0.05) while storing in vacuum packaging. Fraqueza and Barreto (2011) also presented the consistent lightness ( L *) in sliced turkey ham stored in aerobic conditions. In regards to yellowness, Altuntas and Turhan (2013) and Maqsood et al (2016) found no significant changes in beef patties and camel meat under aerobic packaging and vacuum packaging throughout the refrigerated storage.…”
Section: Resultsmentioning
confidence: 82%
“…This result was consistent with Maqsood et al (2016), in which L * values of camel meat remained the same ( p > 0.05) while storing in vacuum packaging. Fraqueza and Barreto (2011) also presented the consistent lightness ( L *) in sliced turkey ham stored in aerobic conditions. In regards to yellowness, Altuntas and Turhan (2013) and Maqsood et al (2016) found no significant changes in beef patties and camel meat under aerobic packaging and vacuum packaging throughout the refrigerated storage.…”
Section: Resultsmentioning
confidence: 82%
“…These researchers have demonstrated that the inclusion of CO along with anoxic gas mixtures for turkey meat under MAP imparted bright pink color preferred by consumers without leading to the appearance of undercooked meat. However, unlike in beef (Uboldi et al, 2015) and pork (Krause et al, 2003), the protective antioxidant effect of anaerobic MAP with CO was not observed in turkey breast muscles after 12 d of storage (Fraqueza and Barreto, 2011). The use of turkey breast muscles, which are lower in lipid and myoglobin content, may have contributed to the lack of effect on lipid oxidation with CO-MAP compared with other MAP.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, when used along with other gases such as CO, nitrogen (N 2 ), and CO 2 , meat has better flavor acceptability, no bone darkening, no premature browning during cooking, and improved tenderness (John et al, 2005;Cornforth and Hunt, 2008;Suman et al, 2011;Denzer et al, 2020;Cassens et al, 2021). Fraqueza and Barreto (2011) reported a shelf life of 25 d for turkey fillets stored at 0°C under MAP consisting of 0.5% CO, 80% CO 2 , and 19.5% N 2 relative to 5 d of shelf life for aerobically packaged meat. These researchers have demonstrated that the inclusion of CO along with anoxic gas mixtures for turkey meat under MAP imparted bright pink color preferred by consumers without leading to the appearance of undercooked meat.…”
Section: Introductionmentioning
confidence: 99%
“…Is an ideal promoter for the growth and proliferation of aerobic microorganisms such as yeasts and molds (Dey & Neogi, 2019). Hence the importance to monitor the oxygen levels inside the food package, to minimizes rancidity, retards lipid oxidation, without any damage to sensory or nutritional properties, resulting in maintaining the quality and shelf life of meat products (Fraqueza & Barreto, 2011).…”
Section: Oxygen Absorbersmentioning
confidence: 99%